1985
DOI: 10.1128/aac.27.6.985
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of multicopy plasmid R6K by bleomycin

Abstract: Bleomycin eliminated multicopy plasmid R6K from growing cells of Escherichia coli AB1157 but failed to cure either of the low-copy plasmids R1 or R46. Measurements of R6K-encoded beta-lactamase and of covalently closed plasmid DNA indicated that the drug causes a progressive reduction in plasmid copy number.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…It is believed bleomycin chelate metal ions (primarily iron) producing a pseudo enzyme that reacts with oxygen to produce superoxide and hydroxide free radicles that cleave DNA [29]. Our results coincide with [30] who used bleomycin to eliminate multi copy plasmid R6K from growing cells of E. coli AB1157. Measurement of R6K-encoded β-lactamase and covalently closed plasmid DNA indicated that the drug causes a progressive reduction in plasmid copy number.…”
Section: By Bleomycinsupporting
confidence: 86%
“…It is believed bleomycin chelate metal ions (primarily iron) producing a pseudo enzyme that reacts with oxygen to produce superoxide and hydroxide free radicles that cleave DNA [29]. Our results coincide with [30] who used bleomycin to eliminate multi copy plasmid R6K from growing cells of E. coli AB1157. Measurement of R6K-encoded β-lactamase and covalently closed plasmid DNA indicated that the drug causes a progressive reduction in plasmid copy number.…”
Section: By Bleomycinsupporting
confidence: 86%
“…Rotimi and Duerden (1982) reported action of acridine dye on E.coli R + and Bacteroides fragillis cells leading to complete loss of Rfactor. Pan et al (1981), Attfield and Pinney (1985) used mytomicin C and bleomycin treatment for curing multicopy plasmid. The relation of plasmid in development resistance was studied by Pan et al (1981) in Enterobacter aerogenes against mercury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above mechanism, it has been reported that copy number and mode of replication control of particular plasmids may play an important role as to whether a plasmid can be cured or not (Attfield et a/., 1985;Danilevskaya et at., 1980). This might be the reason for failure to eliminate R-factors from some of the E. colistrains.…”
Section: Discussionmentioning
confidence: 99%